Challenging the Autonomous Wall: Literacy Work in an Urban High School. (June 2021) - Larson, Joanne; Duret, Eleni; Rees, Jennifer; Anderson, Jessica
This article explores how one urban high school under threat of state closure developed a multifaceted literacy program to transform the teaching and learning of literacy in a novel university/school partnership. Analyses of ethnographic and quantitative school data illustrate how the evolution of the literacy program could be understood as a consequence of generative frictions which produced changes in the program and some indication of changes in understanding of literacy and of students' needs. We weave a story of multiple layers of changed curriculum, scheduling, assessments, and pedagogy to argue that we need to rethink the continuum of autonomous and ideological literacy to focus more on what the intersections of literacy ideologies generate.